Analysis of Gill Structure from a Fresh Water Fish (Heteropneustes fossilis) Exposed to Bleached Sulfite Pulp Mill Effluents. (23rd March 2015) - Dey, Sudip; Rajguru, Utpal; Pathak, Dinesh Chandra; Goswami, Umesh C.
Abstract: The present communication reports toxic effects of bleached sulfite pulp mill effluents in fish ( Heteropneustes fossilis ) gills, with optical, scanning electron, and transmission electron microscopy. The general adverse effects include dilation of the primary lamellar wall, curling of secondary lamellar terminals, displacement of epithelial cell layers, degeneration of secondary lamella, deposition of mucous, and severe congestion in the gill arch. The significant shortening of secondary lamellae, widening of lamellar tips, and significant decrease in the number of mitochondria in chloride cells as compared to controls are some specific effects of bleached sulfite pulp mill effluents. Scanning electron microscopy demonstrated tearing of tissues in gill lamellae and arches. Transmission electron microscopy revealed membrane distortion of mitochondria in chloride cells, loss of uniformity of microvilli in pavement cells, and abnormalities in nuclear shape in different cells of effluent-exposed fish gills. Toxicity of the bleached sulfite pulp mill effluents and its impact on fish are discussed in the light of existing literature. Further, the importance of microscopy in toxicological evaluation of environmental pollutants is emphasized in view of its specific application potential.